Regular high-nuclearity species from square building blocks: a triangular 3 × [2 × 2] Ni12 complex generated by the self-assembly of three [2 × 2] Ni4 golecular grids - Moroz, Yurii S.; Mokhir, Andriy (Inorganic chemistry, 2012)
A dodecanuclear 3 × [2 × 2] nickel(II) complex has been obtained via the self-association of three tetranuclear [2 × 2] molecular grids. X-ray diffraction shows a “propeller-like” structure of the [Ni4]3 scaffold with a central μ3-hydroxide. The dodecanuclear species remains stable in solution and can be deposited without decomposition on highly ordered pyrolytic graphite surfaces.